Horários de aplicação localizada ou em área total e uso de adjuvantes para o controle de Spodoptera frugiperda (Lepidoptera: Noctuidae) na cultura do milho - Soares, Ariane Morgana Leal [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The larval stage of Spodoptera frugiperda (Lepidoptera: Noctuidae) is the major cause of yield losses in maize. The aim of this study was to evaluate the control of S. frugiperda, during the first infestation, in day and nighttime spraying directed to maize plants whorl and in total area with insecticide spraying liquids supplemented or not by adjuvant as well as analyze physical characteristics of surface tension and contact angle, droplets diameter and volumetric distribution for the two modes of application. The research at field conditions has involved two modes of application (directed to the whorl of plants and to total area), two times (8 a.m. and 8 p.m.), three insecticide spraying liquids (only insecticide, insecticide with nonifenol and insecticide with oil) and a treatment without application following a triple factorial (2x2x3)+1, in a randomized block design with four replications. Sowing was done in seasons 2012/13 and 2013/14, the factors evaluated were larvae alive after application (4, 8 and 12 days) and dry matter of maize plants (g.parcela-1). The surface tension and contact angle were obtained in tensiometer. The droplets diameter was measured by a laser analyzer and the volumetric distribution on patternator. The same spraying liquids from the field experiment were used and compared with water only (same as used for spraying), and ultrapure water, and two models of spray nozzles DG95015 and LD110015. Data were subjected to analysis of variance by F test and the means were compared by Tukey test at 5% probability. It was obtained better control of the insect by the nocturnal directed spraying, regardless of the spraying liquid used, with smaller loss dry matter weight. The addition of adjuvants to insecticide spraying liquids increased wetting and the diameter of sprayed droplets for the two nozzle models, and the volumetric distribution was equivalent for the two application ...

A fase larval do inseto Spodoptera frugiperda (Lepidoptera: Noctuidae) há muitos anos é a principal causa de perdas de produtividade na cultura do milho. O objetivo deste trabalho foi avaliar o controle de S. frugiperda, na primeira infestação, em pulverização diurna e noturna e direcionada ao cartucho das plantas de milho ou em área total, com caldas inseticidas acrescidas ou não de adjuvantes, bem como analisar as características físicas de tensão superficial, ângulo de contato, diâmetro de gotas para as caldas, e distribuição volumétrica para os dois modos de aplicação. Para o desenvolvimento do trabalho em campo, foram utilizados dois modos de aplicação (direcionado ao cartucho das plantas e em área total), dois horários (08 e 20h), três caldas inseticidas (somente com inseticida, inseticida mais nonil fenol e inseticida mais óleo vegetal) e um tratamento sem aplicação, em esquema fatorial triplo (2x2x3)+1, conduzido em delineamento de blocos ao acaso, com quatro repetições. A semeadura foi feita nas safras 2012/13 e 2013/14, sendo avaliados os fatores: lagartas vivas após a aplicação (4, 8 e 12 dias) e matéria seca (g.parcela-1). Em laboratório para análise de tensão superficial e ângulo de contato, utilizou-se de tensiômetro. O diâmetro das partículas foi medido por analisador a laser e a distribuição volumétrica por mesa de deposição. Foram utilizadas as mesmas caldas do experimento de campo e para algumas análises também foram acrescentadas caldas somente com água (mesma utilizada para as pulverizações), água ultra pura e dois modelos de pontas de pulverização DG95015 e LD110015. Os dados foram submetidos à análise de variância pelo teste F e as médias comparadas pelo teste de Tukey a 5% de probabilidade. Houve maior controle do inseto pela pulverização noturna e direcionada ao cartucho das plantas de milho, independente da calda ...
Keywords: Milho; Milho - Doenças e pragas - Controle; Lagarta; Defensivos vegetais - Tecnologia de aplicação; Pulverização; Spraying